Age- and Sex-Specific Increases in Stimulant Prescribing Rates—California, 2008-2017. Issue 2 (January 2020) - Tseregounis, Iraklis Erik; Stewart, Susan L.; Crawford, Andrew; Marshall, Brandon D. L.; Cerdá, Magdalena; Shev, Aaron B.; Henry, Stephen G.
Objective: To describe trends in prevalent and incident stimulant prescribing between 2008 and 2017 in California.Method: Statewide trends were estimated by age and sex category for prevalent (any) and incident (no prescriptions in the preceding 2 years) stimulant prescribing while adjusting for area-level covariates.Results: Prevalent prescribing rates increased by 126%, while incident prescribing increased 23%. Patients aged 25 to 44 years experienced over 200% increases in prevalent prescribing and 34% to 55% increases in incident prescribing. Among patients older than 25, women had consistently higher prescribing rates than men. ZIP code tabulation areas with the largest minority populations had the lowest baseline prescribing rates but experienced the greatest annual prescription rate increases.Conclusion: Adult stimulant prescribing increased substantially for early working aged adults. Prescription rates were greater for women than men.